2014
DOI: 10.4314/ejhs.v24i1.4
|View full text |Cite
|
Sign up to set email alerts
|

Head Injury-A Neglected Public Health Problem: A Four-Month Prospective Study at Jimma University Specialized Hospital, Ethiopia

Abstract: BackgroundTrauma, especially head trauma, is an expanding major public health problem and the leading cause of death of the young and productive part of the world's population. Research is mainly done in high-income countries where only a small proportion of the worldwide fatalities occur. The intention of this study was to analyze head injury in a setting where most patients in low- and middle-income countries receive treatment, a referral hospital with general but no neurosurgical service like Jimma Universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 22 publications
5
44
2
Order By: Relevance
“…This is the similar to a study in Ethiopia, where there are 47 males out of 52 HI patients (90.4%). 11 This result is also similar to the study in United Arab Emirates, where there are 521 males out of 589 HI patients (88.3%). 2 The result in this study may be due to the less exposure to risk factors of HI in females as they prefer to stay in the house compared to males.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This is the similar to a study in Ethiopia, where there are 47 males out of 52 HI patients (90.4%). 11 This result is also similar to the study in United Arab Emirates, where there are 521 males out of 589 HI patients (88.3%). 2 The result in this study may be due to the less exposure to risk factors of HI in females as they prefer to stay in the house compared to males.…”
Section: Discussionsupporting
confidence: 88%
“…10 The lowest cause of HI in this study is assault (5%), which is different to a study in Ethiopia (2014), where fights is the highest cause of HI (38.5%). 11 The difference of results may be caused by considerable variations due to different study locations. 4 Two-wheelers motor vehicle is the highest cause of RTAs in patients with HI in this study (68%).…”
Section: Discussionmentioning
confidence: 99%
“…Several authors in the literature [10][11][12][13][14] have reported the young age and the male predominance found in this study. Traumatic brain injuries remain a major problem affecting the young subjects and thus handicaps the social and especially economic development of low-income countries such as ours.…”
Section: Epidemiological Characteristicssupporting
confidence: 67%
“…These findings are consistent with a study in Ethiopia, where RTIs were the second major cause of head injuries after interpersonal fights. 18 Our study findings have a number of policy and practice implications. First, they highlight the importance for EDs and referral departments (surgical departments in particular) to increase their capacity for RTI-related admissions during the holiday periods.…”
Section: Public Health Action Rtis In Addis Ababa Ethiopia 69mentioning
confidence: 81%